2021
DOI: 10.5435/jaaos-d-20-00637
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Effects of Musculoskeletal Trauma

Abstract: Musculoskeletal injuries comprise a large percentage of hospital admissions for adults and often contribute to persistent daily pain as an illness; opioid dependence; disability; and complaints of increased depression, anxiety, and symptoms of post-traumatic stress disorder. The prevalence of depression and post-traumatic stress disorder after orthopaedic trauma has been found to be considerably greater than the general adult cohort. Soon after sustaining a fracture, psychological factors can predict pain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…Findings are consistent with previous research that has found that the nature of work and types of accidents and injuries workers experience are related to development of PTSI 1,5 . Our sample of workers with concurrent MSI and PTSI also reported worse general health and worse social functioning and had less attachment to the workplace (including being less likely to be working at admission and discharge from rehabilitation), which is consistent with previous research 3,4 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Findings are consistent with previous research that has found that the nature of work and types of accidents and injuries workers experience are related to development of PTSI 1,5 . Our sample of workers with concurrent MSI and PTSI also reported worse general health and worse social functioning and had less attachment to the workplace (including being less likely to be working at admission and discharge from rehabilitation), which is consistent with previous research 3,4 .…”
Section: Discussionsupporting
confidence: 92%
“…Workers experiencing traumatic musculoskeletal injury (MSI) are at risk of developing posttraumatic stress injury (PTSI). 1 The prevalence of posttraumatic stress after acute orthopedic trauma varies from study to study, but a recent meta-analysis of patients with acute orthopedic injuries reported a weighted pooled prevalence of diagnosed posttraumatic stress disorder of 26% (95% confidence interval [CI], 19.0%–35.9%). 2 Workers with concurrent MSI and PTSI are also more likely to experience delayed recovery, including being less likely to return to work.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Having a serious injury might, in itself, be sufficient to increase the risk of suffering from anxiety, in fact a recent systematic review indicates that 11% to 56% of individuals who have sustained orthopedic trauma suffer from some form of anxiety symptoms up to 10 years after the injury (Breazeale, Conley, Gaiser, & Redeker, 2021). Pain, depression and PTSD are also common after musculoskeletal trauma (Kang, Ciminero, Parry, & Mauffrey, 2021). Future research could investigate the qualitative nature of anxiety sources after mTBI specifically, as well as common factors shared with other types of physical injuries.…”
Section: Discussionmentioning
confidence: 99%